Sinergias entre as instabilidades climáticas e a produção de leite no Ceará - Alves, Leopoldina Braga (2024)
The State of Ceará is situated in a geographical area characterized by diverse landscapes, terrains, and rainfall patterns, among other features. Based on these characteristics, the Fundação Cearense de Meteorologia e Recursos Hídricos (FUNCEME) has subdivided the state into eight climatic regions. The research addresses the following questions: 1. How do climatic variables interact with those that define milk production in the state and in the eight climatic regions of Ceará? 2. Is it accurate to assert that the producers with higher production levels, as defined by the set of variables influencing milk production, incurred greater risks during the study period? This study examined the heterogeneity of milk production in the state and its respective regions from 1997 to 2020. To answer these questions, the research aims to: a) Evaluate the descriptive statistics of climatic variables and factors impacting the value of milk production in Ceará from 1997 to 2020, including the examination of instabilities associated with these variables across different climatic regions of the state; b) Create the Temporal Instability Index (INST) and the Production Index (IPRO) to capture the synergies between climatic variables and those defining milk production in the municipalities of Ceará from 1997 to 2020; c) Rank the state's climatic regions according to these two instruments; d) Measure the relationship between IPRO and INST in the state and its climatic regions. The data used were obtained from the Municipal Livestock Production (PPM) reports, IBGE statistical yearbooks, and the National Oceanic and Atmospheric Administration (NOAA). The methodological procedures include estimating the descriptive statistics of the variables defining milk production in the municipalities of Ceará, as well as rainfall and temperature data. The study estimates the climatic instabilities and the variables defining milk production over the period. To develop the IPRO and INST for the state's milk production, with subdivisions for the climatic regions, a factor analysis method with principal component decomposition is employed. To assess the relationship between these indices, Pearson's Correlation Coefficient is used. The results showed good statistical adjustments. Based on the IPRO, the climatic regions are grouped into six, each expressing distinct average milk production indicators. Regarding the INST, the findings grouped the eight climatic regions into four, each representing varied aggregated instabilities. The study results confirmed Markowitz's hypothesis that higher average production levels (including climatic variables) are associated with greater instabilities and, consequently, higher risks